Phylogeny, karyotype evolution and taxonomy of Crocus series Verni (Iridaceae) - Harpke, Dörte; Carta, Angelino; Tomović, Gordana; Ranđelović, Vladimir; Ranđelović, Novica; Blattner, Frank R; Peruzzi, Lorenzo (Plant systematics and evolution, 2015)
The taxonomically complicated Crocus series Verni is characterized by high intra- and interspecific variability of karyotypes (2n = 8–23). With the aim to get more insights into complex karyotype evolution and to clarify the taxonomy of this group, we combined morphological (twelve characters), molecular (chloroplast DNA: trnL–trnF, ndhF; nuclear DNA: ITS, pCOSAt103) and karyological analyses. Samples of different populations of C. etruscus, C. ilvensis, C. kosaninii, C. tommasinianus, C. vernus sensu lato and C. longiflorus (series Longiflori) were analyzed. Quantitative karyotype parameters were calculated for all taxa involved based on the available literature. For the taxon traditionally known as C. vernus, the analyses suggest that it should be split in five species: C. heuffelianus, C. neapolitanus, C. neglectus sp. nov., C. siculus and C. vernus. The comparison of genome total haploid lengths suggests that in the evolution of the group polyploidization only played a role within the C. vernus species complex, where we also detected two hybridization events. In all other taxa, chromosome evolution is probably characterized by chromosome fusions and fissions, sometimes affecting the entire haploid chromosome set. Comparative cytogenetics of the group indicates that series Verni is subject to a peculiar type of unequal change in chromosome size, i.e., that not both chromosome arms gain or lose equally in DNA content. As a taxonomic consequence of our study, series Verni is newly circumscribed, now including the autumn-flowering C. longiflorus and excluding C. baytopiorum.